Case Report: Increase in wall shear stress in a narrowed true lumen after type A aortic dissection repair analyzed by computed fluid dynamics - Iida, Yasunori; Marushita, Yoichi; Motohashi, Yuka; Sato, Toshio (Frontiers in Cardiovascular Medicine, 2024)
A 46-year-old man suffered from acute type A aortic dissection (TAAD) and underwent total arch replacement using the frozen elephant trunk (FET) procedure. During follow-up, we noted back pain and found distal stent graft-induced new entry (dSINE) at the FET distal part by computed tomography. We performed additional extended thoracic endovascular aortic repair (TEVAR) for this pathology. The time between TAAD repair and TEVAR was 2 months. We investigated this complication by computational fluid dynamics analysis through pre- and post-dSINE. The results showed increased wall shear stress at the narrowed true lumen (TL) site, not at the FET site, indicating that prestenotic hydrodynamic load may affect dSINE occurrence.